Implementation strategies: lessons learned during an e-learning intervention to improve dietary behaviors and feeding practices in early childhood education and care - Henrik Lian; Nina Cecilie Øverby; Frøydis Nordgård Vik; Anine Christine Medin; Natalie Garzon Osorio; Christine Helle; Tormod Bjørkkjær; Penelope Love; Harry Rutter; Mary Elizabeth Barker; Elisabet Rudjord Hillesund; Sissel Heidi Helland (BMC Nutrition, 2025)
Abstract Background Early Childhood Education and Care (ECEC) centers play an important role in fostering healthy dietary habits. The Nutrition Now project focusing on improving dietary habits during the first 1000 days of life. Central to the project is the implementation of an e-learning resource aimed at promoting feeding practices among staff and healthy dietary behaviours for children aged 0–3 years in ECEC. Implementing new interventions often presents challenges. This study explores ECEC staff views and experiences with selected strategies for implementing an e-learning resource in ECEC centers in a municipality in Southern Norway. Methods The study is a part of the Nutrition Now study, a hybrid type 1 non-randomized controlled trial. The implementation process followed the Dynamic Integrated Evaluation Model (DIEM). Implementation strategies were selected from the Expert Recommendations for Implementing Change (ERIC) project and included identify and prepare champions, conduct educational meetings, distribute educational materials, create a learning collaborative, and remind clinicians. ECEC teachers from participating ECEC centers in the intervention municipality were recruited as champions. Brief (5–7 min minutes), semi-structured phone interviews, covering key points, were conducted with the champions 8 times, evenly distributed over six months. The interviews were analysed using qualitative thematic analysis. Results In total, 29 of the invited ECEC centers (53%) participated, and 260 brief interviews (88%) were conducted with champions (n = 37). An evaluation of the feedback from the champions suggests that the five selected implementation strategies were acceptable. Five main themes were developed by qualitative analysis: 1) Being a champion resembles what I already do. 2) Educational meetings are fine but take time. I prefer when peers share experiences. 3) Newsletters were helpful and reminded me, but I do not always have enough time to read. 4) Evaluations have increased my awareness, and we do them informally and formally. 5) The regular phone calls reminded me I could receive support and express my opinion. Conclusion This study’s findings suggest that several implementation strategies are acceptable for stakeholders in an ECEC e-learning healthy eating intervention. However, time constraints among champions may hinder deep engagement. These results provide valuable insights into how the selected implementation strategies may function in practice and how they are perceived and experienced by the ECECs staff. Trial registration Trial registration on June 6, 2022: ISRCTN10694967 .